2004
DOI: 10.1124/mol.104.005447
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-aspartate and Brain-Derived Neurotrophic Factor Induce Distinct Profiles of Extracellular Signal-Regulated Kinase, Mitogen- and Stress-Activated Kinase, and Ribosomal S6 Kinase Phosphorylation in Cortical Neurons

Abstract: Stimulation of N-methyl-D-aspartate (NMDA) receptors is believed to underlie long-term memory formation, and excessive NMDA receptor activation has been linked to several neuropathological conditions. Phosphorylation and activation of p42/44 mitogen-activated protein kinase (ERK) is believed to mediate many of these effects, but the downstream targets of ERK in response to NMDA activation have not been determined. In primary cultures of rat cortical neurons, we found that NMDA was able to elevate phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…These data are in agreement with previous studies, in which a similar MSK1 kinetic activation was observed upon stimulation of different cell types (Hela, SK-N-MC, PC12, cardiac myocytes and embryonic rat cortical cells) with various agonists including tumor necrosis factor, fibroblast growth factor, neuronal growth factor, endothelin-1, N-methyl-D-Aspartate and brain-derived neurotrophic factor [Deak et al, 1998;Markou and Lazou, 2002;Rakhit et al, 2005]. It has recently been defined that Thr 581 residue in the MSK1 C-terminal kinase domain is a prolinedirected site, which can be phosphorylated either by p38 or p42/44 MAPKs [McCoy et al, 2005].…”
Section: Vegf Mediates Msk1 Phosphorylationsupporting
confidence: 93%
“…These data are in agreement with previous studies, in which a similar MSK1 kinetic activation was observed upon stimulation of different cell types (Hela, SK-N-MC, PC12, cardiac myocytes and embryonic rat cortical cells) with various agonists including tumor necrosis factor, fibroblast growth factor, neuronal growth factor, endothelin-1, N-methyl-D-Aspartate and brain-derived neurotrophic factor [Deak et al, 1998;Markou and Lazou, 2002;Rakhit et al, 2005]. It has recently been defined that Thr 581 residue in the MSK1 C-terminal kinase domain is a prolinedirected site, which can be phosphorylated either by p38 or p42/44 MAPKs [McCoy et al, 2005].…”
Section: Vegf Mediates Msk1 Phosphorylationsupporting
confidence: 93%
“…Membrane-bound secondary antibodies were detected using the ECL Plus procedure developed by GE Healthcare Life Sciences. Integrative optical density readings were obtained using NIH Image (W. Rasband, National Institutes of Health, Bethesda, MD), and differences in specific density between RhoB ϩ/ϩ and mutant animals were analyzed for statistical significance as described (Rakhit et al, 2005;James et al, 2006). Where the number of samples was too great to be run on a single gel, band intensities were expressed as a percentage of the mean band intensity from the control RhoB ϩ/ϩ group on that gel.…”
Section: Methodsmentioning
confidence: 99%
“…48 IEG induction is known to be strongly regulated via the MEK-ERK pathway, 49,50 which is also one of the main effectors of BDNF signaling. 51,52 Hence, we propose that the IEG transcript downregulations we see in the BDNF-deficient animals are due to the lack of release of BDNF and impaired trophic support. 53,54 Second, the cyclin-dependent kinase inhibitor 1C (CDKN1c) and cyclin D2 (CCND2) also showed Figure 3 Expression changes specific for mice with the embryonic deletion of brain-derived neurotrophic factor (BDNF).…”
Section: Discussionmentioning
confidence: 85%